Implementation of DG for loss minimization and voltage profile in distribution system - Siti Rafidah, Abd Rahim; Titik Khawa, Abdul Rahman, Prof. Dr.; Ismail, Musirin, Dr.; Muhd Hatta, Hussain; Mohd Herwan, Sulaiman; Omar, Aliman; Zainuddin, Mat Isa (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/